Upaya Mahasiswa Papua Universitas Jember Pengrajin Noken Dalam Melestarikan Kearifan Lokal di Daerah Perantauan - Mote, Gustaviana Touye Magaa (Politeknik Pengayoman Indonesia, 2026)
Noken is a cultural heritage of the Papuan people that embodies philosophical, social, and symbolic values and has been recognized by UNESCO as an Intangible Cultural Heritage since 2012. However, in migration contexts, noken is often perceived merely as a handicraft, causing its cultural meanings to be overlooked. This study aims to describe the efforts of Papuan students at the University of Jember who craft noken in preserving local wisdom while living in diaspora, particularly in Jember Regency. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and documentation. Informants include Papuan student noken artisans, Papuan students involved in cultural activities, and a cultural activist. Data were analyzed using the Miles and Huberman model, consisting of data condensation, data display, and conclusion drawing, with triangulation to ensure data validity. The findings show that Papuan students preserve noken through handmade production, design innovation, social media promotion, daily use of noken, cultural education, and participation in festivals and bazaars. Challenges include limited raw materials, time constraints, minimal institutional support, and low public understanding of noken’s philosophical values. This study concludes that Papuan students act as cultural diaspora agents who sustain and adapt local wisdom in modern life.